BAKTI SOSIAL PEMERIKSAAN KESEHATAN MATA KEPADA MASYARAKAT DI BANJAR JAGATAMU, DESA MELILING, KERAMBITAN, TABANAN OLEH FAKULTAS KEDOKTERAN UNIVERSITAS MAHASARASWATI DENPASAR - Ni Made Widya Mahayani; Ni Made Putri Suastari; AA Sagung Candra Mahesuari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The social service of eye health is one form of community service aimed at raising awareness and improving the quality of public health, especially eye health. This activity was carried out by the Faculty of Medicine, Universitas Mahasaraswati Denpasar, in Banjar Jagatamu, Desa Meliling, Kerambitan, Tabanan. The purpose of the eye health screening was to detect early visual disturbances that may affect the quality of life of the community, as well as to provide education on the importance of maintaining eye health. The activities included physical eye examinations, visual acuity tests, provision of reading glasses, distribution of eye drops for those in need, and referrals for further treatment if necessary. The results of this activity showed that the majority of the community in the area requires more accessible eye health services. It is hoped that this social service will have a positive impact in raising public awareness about the importance of eye health care and facilitate better access to medical treatment.